Migrations and culture. Essential reflections on wandering human beings - Contini, Paolo; Carrera, Letizia (Frontiers in Sociology, 2022)
It is possible that our century and the one just past will be remembered in the future as the centuries of migration. Faced with the extent of migration today, social scientists have posed several questions, and in particular they have examined the causes of migration, the integration of immigrants into host countries, and the development of their cultural identity. The newcomers are almost always poorer than those who settled before them, and have different languages, physical appearance, customs, beliefs, and religious practices. The widespread perception is that of an upheaval of the social order. For some, it is the dawn of a new world, under the banner of métissage (or hybridization) and universal brotherhood; for most, it is the beginning of an invasion. Immigration is always a matter of borders: Who is “us”? Who is “them”? The host society has the power to define, classify, and construct the social category of immigrants. There are many differences within this category and obviously any strategic policy should be able to manage every specificity. Nevertheless, we need starting by focusing the more general ideal type of what is “otherness” and what it can be in the social representations in order to construct new conditions of encounter. In this scenario, urban spaces represent the stages on which the encounter with difference takes place. The space is never neutral and may affect, sometimes significantly, the conditions of that encounter. The physical form of the city is the result of widespread social representations of all phenomena, but it is also able to act on those same social representations by altering the processes that take shape within it. The urban dimension and the redesign of the urban space become increasingly key to shaping and managing social processes aimed at governing the transformation processes in a multi-ethnic sense of the European societies. Urban policy-makers can either wait for spontaneous processes of integration and virtuous composition of differences, or implement actions to manage differences, to prevent potential conflicts and start processes of active inclusion. In order to support the act of wandering within this second pattern of urban policies, moving from simple tolerance to a Habermasian process of dialogical exchange, at least two conditions are necessary: the existence of shared public spaces, and the quality of policies for regulating the use of urban public spaces.